Los folletos como agentes del debate político: ciudad de México, 1821-1855 - Soberón Mora, Arturo (2014)
Folletos and other kinds of printed matter, such as loose sheets or volantes, played a leading role in the emerging political struggles of the nineteenth century. In recent years, interest in studying print culture of the late eighteenth and early nineteenth century has motivated numerous essays in Latin American fields on different aspects of the subject. This article seeks to highlight the transformation which folletos and their contents experienced in the late colonial period and, consequently, the prominent role that these documents had in the intense debate that characterized the political contests of the early decades of independent Mexico.